Peran Badan Pengawas Obat dan Makanan terhadap Peredaran Obat Tradisional yang Mengandung Bahan Kimia Obat Berbahaya dalam Perlindungan Konsumen - Imam Cahyono; Marsitiningsih Marsitiningsih; Selamat Widodo (Universitas Muhammadiyah Purwokerto, 2019)
The role of the Food and Drug Supervisory Agency (BPOM) in carrying out its duties, functions and authority is solely to protect the rights of every consumer. The supervision carried out by BPOM is Pre-Market (preliminary supervision carried out before a product is circulated in the community) and Post Market supervision (supervision carried out after the product is circulated in the community). The supervision that has been carried out is still not running optimally and it is not possible to know the distribution of traditional medicinal products containing medicinal chemicals. The purpose of this study was to determine the role of the Food and Drug Administration in dealing with the distribution of traditional medicines containing chemicals. This research is a normative juridical research by obtaining data from books, journals, research results and related laws and regulations. The results of the study show various statutory regulations, government regulations and regional regulations. In order to supervise the distribution of traditional medicines containing medicinal chemicals, the food and drug supervisory agency should be tightened and carry out routine checks in every district or city.Keywords: Food and Drug Supervisory Agency (BPOM), Traditional Medicine, Medicinal Chemistry